Preservice Physics Teacher Views on Scientist's Role in Physics Teaching and Learning - Nurul Fitriyah Sulaeman; Atin Nuryadin; Shelly Efwinda; Lambang Subagiyo; Syayidah Dinurrohmah; Tan Fahrur Rozy Tandra; Tomohiro Takebayashi (Universitas Lambung Mangkurat, 2024)
This qualitative study explores how preservice physics teachers think about the role that scientists play in the teaching and learning of physics. Our participants were 33 preservice physics teachers in their first year participating in a scientist partnership program through online meetings. Participants' responses were collected through an essay questionnaire, and the result was analyzed with co-occurrence network analysis. Our research shows that preservice physics teachers have a positive perspective on scientists. The primary role of a scientist is related to a person with sufficient knowledge and opinion about physics. Their role is also related to the experiment and research result. Moreover, their innovation and discovery of new physics-related things also became their central role. After preservice physics teachers interact with scientists, they have higher motivation to learn physics. Our findings suggest that the activity facilitating interaction with professional scientists must be encouraged during the preservice physics teacher program.